2015
DOI: 10.1111/cdev.12461
|View full text |Cite
|
Sign up to set email alerts
|

Individual Differences in Statistical Learning Predict Children's Comprehension of Syntax

Abstract: Variability in children's language acquisition is likely due to a number of cognitive and social variables. The current study investigated whether individual differences in statistical learning (SL), which has been implicated in language acquisition, independently predicted 6- to 8-year-old's comprehension of syntax. Sixty-eight (N = 68) English-speaking children completed a test of comprehension of four syntactic structures, a test of SL utilizing nonlinguistic visual stimuli, and several additional control m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
167
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 157 publications
(185 citation statements)
references
References 80 publications
15
167
1
2
Order By: Relevance
“…Indeed, infants' processing speed in sequential learning tasks predicts vocabulary size months later (Ellis et al 2014). Studies with child learners suggest a similar pattern of results: 6- to 8-year-olds' visual statistical learning skills predict their level of performance on measures of native language syntax comprehension (Kidd & Arciuli 2016). Research investigating the relationship between visual attention in infancy (from a visual pattern prediction task) and later childhood behavior and temperament showed that mean fixation duration infancy was positively associated with effortful control and negatively associated with surgency, hyperactivity, and inattention in childhood (Papageorgiou et al 2014).…”
Section: Real-world Problemsmentioning
confidence: 85%
“…Indeed, infants' processing speed in sequential learning tasks predicts vocabulary size months later (Ellis et al 2014). Studies with child learners suggest a similar pattern of results: 6- to 8-year-olds' visual statistical learning skills predict their level of performance on measures of native language syntax comprehension (Kidd & Arciuli 2016). Research investigating the relationship between visual attention in infancy (from a visual pattern prediction task) and later childhood behavior and temperament showed that mean fixation duration infancy was positively associated with effortful control and negatively associated with surgency, hyperactivity, and inattention in childhood (Papageorgiou et al 2014).…”
Section: Real-world Problemsmentioning
confidence: 85%
“…These probabilistic cues may be analyzed via SL, the process of using co-occurrence to group elements in the environment. IDs in SL have been linked to language proficiency across the lifespan, a relationship that has been attested across multiple domains of language, including vocabulary [105], grammatical [106], and literacy development in children [107]; and second language-learning adults [108]. The link is also attested in adults, and appears most strongly in tasks involving predictability; for instance, in predicting likely continuations of sentences in context [109] or in grammatical sequencing [110][111][112].…”
Section: Interestingly Wm and Ef Are Interrelated (See Outstanding Qmentioning
confidence: 99%
“…Specifically, SL is suggested to provide a potentially powerful mechanism with which children can acquire language from input without strong assumptions about innateness (although see [16]). More recently, the field has attempted to quantify IDs in SL, and has linked these to language proficiency in children and adults [105][106][107][108][109][110][111][112]132]. This work has shown some promise, with mostly medium-positive associations between SL and language typically reported [133].…”
Section: Box 1 Ids In Statistical Learning and Their Relationship Tomentioning
confidence: 99%
“…For example, Evans et al [22], Conway et al [20] and Kidd & Arciuli [26] found that tasks of sequential SL were tapping into abilities that were independent of those assessed by tests of non-verbal intelligence. Kaufman et al [24] found that variability in SL was independent of variability in general intelligence and WM but related to variability in processing speed.…”
Section: Multiple Components Underpinning Statistical Learningmentioning
confidence: 99%
“…[19][20][21][22][23][24][25][26][27][28]). Better performance on independent tasks of SL tends to be associated with greater language proficiency.…”
Section: Introductionmentioning
confidence: 99%